Genomic, proteomic, and transcriptomic analysis of virulent and avirulent Rickettsia prowazekii reveals its adaptive mutation capabilities - Bechah, Yassina; El Karkouri, Khalid; Mediannikov, Oleg; Leroy, Quentin; Pelletier, Nicolas; Robert, Catherine; Médigue, Claudine; Mege, Jean-Louis; Raoult, Didier (Genome Research, 2010)
Rickettsia prowazekii, the agent of epidemic typhus, is an obligate intracellular bacterium that is transmitted to human beings by the body louse. Several strains that differ considerably in virulence are recognized, but the genetic basis for these variations has remained unknown since the initial description of the avirulent vaccine strain nearly 70 yr ago. We use a recently developed murine model of epidemic typhus and transcriptomic, proteomic, and genetic techniques to identify the factors associated with virulence. We identified four phenotypes of R. prowazekii that differed in virulence, associated with the up-regulation of antiapoptotic genes or the interferon I pathway in the host cells. Transcriptional and proteomic analyses of R. prowazekii surface protein expression and protein methylation varied with virulence. By sequencing a virulent strain and using comparative genomics, we found hotspots of mutations in homopolymeric tracts of poly(A) and poly(T) in eight genes in an avirulent strain that split and inactivated these genes. These included recO, putative methyltransferase, and exported protein. Passage of the avirulent Madrid E strain in cells or in experimental animals was associated with a cascade of gene reactivations, beginning with recO, that restored the virulent phenotype. An area of genomic plasticity appears to determine virulence in R. prowazekii and represents an example of adaptive mutation for this pathogen.